The Role of IL-33-Dependent Inflammation in the Tumor Microenvironment - Wasmer, Marie-Hélène; Krebs, Philippe (Frontiers in Immunology, 2017)
There is compelling evidence that inflammation contributes to tumorigenesis. Inflammatory mediators within the tumor microenvironment can either promote an antitumor immune response or support tumor pathogenesis. Therefore, it is critical to determine the relative contribution of tumor-associated inflammatory pathways to cancer development. Interleukin-33 (IL-33) is a member of the IL-1 family of cytokines that is released upon tissue stress or damage to operate as an alarmin. IL-33 has been primarily implicated in the induction of type-2 immune responses. However, recent findings have shown a role of IL-33 in several cancers where it may exert multiple functions. In this review we will present the current knowledge on the role of IL-33 in the microenvironment of different tumors. We will highlight which cells produce and which cells are activated by IL-33 in cancer. Furthermore, we will explain how IL-33 modulates the tumor-associated inflammatory microenvironment to restrain or promote tumorigenesis. Lastly, we will discuss the issues to be addressed first before potentially targeting the IL-33 pathway for cancer therapy.